2018
DOI: 10.1039/c7nr08878g
|View full text |Cite
|
Sign up to set email alerts
|

Electrically enhanced hot hole driven oxidation catalysis at the interface of a plasmon–exciton hybrid

Abstract: In this work, an electro-optical device based on a graphene-Ag nanoparticle hybrid is fabricated as the substrate of graphene mediated surface enhanced Raman scattering (G-SERS) manipulated by the gate and bias voltages. Plasmon-exciton coupling promotes co-driven surface catalytic reactions, where the density of states (DOS) of holes and electrons on graphene is well controlled by the gate voltage, and the kinetic energy of holes and electrons is driven by the bias voltage (or current). Our experimental resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
92
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(93 citation statements)
references
References 35 publications
0
92
1
Order By: Relevance
“…Graphene is the carrier transport channel, and PbS CQDs are used as the photon absorbing material ( Figure a). The unique electronic properties of graphene offer a gate‐tuneable carrier density and polarity that enable us to tune the sensitivity and operation speed of the detector . Figure b shows the photocurrent response of the decorated phototransistor under illumination at room temperature in ambient, which is measured with a focused laser beam with a wavelength of 1550 nm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Graphene is the carrier transport channel, and PbS CQDs are used as the photon absorbing material ( Figure a). The unique electronic properties of graphene offer a gate‐tuneable carrier density and polarity that enable us to tune the sensitivity and operation speed of the detector . Figure b shows the photocurrent response of the decorated phototransistor under illumination at room temperature in ambient, which is measured with a focused laser beam with a wavelength of 1550 nm.…”
Section: Resultsmentioning
confidence: 99%
“…0D materials such as IV–VI group quantum dots show excellent light harvesting capability in the infrared region and can be conveniently integrated with silicon substrates via a solution process . Recently, hybrid graphene‐CQD phototransistors which combine the high mobility of graphene and strongly light‐absorbing absorbance of CQDs have been explored for enhancing both the photo‐responsivity and the gain of the photodetector and the detected wavelength can extend into the shortwave infrared (SWIR) region (≈1550 nm) . Photo‐generated charges in CQDs can transfer to graphene, while oppositely charged carriers remain trapped in the quantum‐dot layer.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding transformations involving charge transfer of LSPR‐excited hot electrons and holes to surface adsorbates, a unifying treatment has been recently proposed . In this case, it has been shown that hot electrons can participate in LSPR‐driven reduction reactions and the holes can assist LSPR‐driven oxidations ,. While Ag, Au, Cu, and Al based NPs have attracted attention as catalysts,,,, only few studies have focused on the establishment of proper structure‐performance relationships.…”
Section: Introductionmentioning
confidence: 99%
“…This conclusion is powerful evidence for the interpretation of the disappearance of IR-active modes in SERS. In previous SERS experiments, dimerization of p-aminothiophenol (PATP) to DMAB was an ideal candidate for revealing plasmon-driven catalytic reactions [16,[70][71][72][73][74][75][76]. Both theoretical simulations and experimental observations have been investigated in detail, while the dynamic process of the dimerization needs further investigation [77][78][79][80].…”
Section: Au Ters For Plasmon-driven Synthesis Catalysismentioning
confidence: 99%